Bioabsorbable fixation system as an alternative for the treatment of mandibular fractures in pediatric patients: literature review - Ribeiro, Enya Laissah Freire (2022)
Although facial fractures in pediatric patients are uncommon due to bone elasticity, the mandible has a high prevalence in pediatric trauma. Metal fixation systems are conventionally used to treat mandibular fractures. However, their applications have been questioned in this patient profile because they have disadvantages such as limitation in mandibular growth, potential to cause infections and possible need for a second surgical procedure for their removal. The present study aims to know the particularities of the pediatric mandible, understand the functioning of bioabsorbable plates and discuss the positive and negative points of their use in the treatment of mandibular fractures. This is a narrative literature review carried out through a vast search in books, monographs and scientific articles from the last 10 years, in the PubMed, MEDLINE and Google Scholar databases, in the "advanced search" mode, using the following descriptors in Portuguese and English: “Mandibular fractures”, “Internal fixation of fractures” and “Pediatrics”. The advent of bioabsorbable fixation systems denotes several benefits regarding their application in the treatment of mandibular fractures in pediatric patients, due to their properties that allow resorption in the fixation system as bone repair is established. It was possible to consider that the use of bioabsorbable fixation as a treatment for mandibular fractures in children is a viable alternative, presenting benefits for not compromising mandibular growth, reinforcing the importance of carrying out future research in order to obtain higher levels of scientific evidence.